Management of the activity of quality assurance of cast iron castings in foundries. Issue 1 (February 2021) - Josan, A; Ardelean, E; Ardelean, M; Puţan, V
Abstract: In Romania, at present, the process of casting the parts is used under different methods. Thus, castings have different configurations and are used in various fields of technology, such as for the automotive industry, motorcycles and engines, electrical and electronics, space, computing and office equipment, agricultural machinery, aeronautics, woodworking or household industry. There is also a wide variety of materials used in casting these types of castings. The quality of the castings is found in the final product and, therefore, a special importance is attributed to the management activity to ensure the proper management of all processes in the foundry. For this, methods, techniques and management tools are used and applied so as to continuously optimize processes and activities and to be in accordance with the objectives of the system, respectively the continuous quality assurance and customer satisfaction. The paper presents the possibility of obtaining the quality of vermicular graphite cast iron castings, of the gate valve type.